PERTUMBUHAN VEGETATIF DAN GENERATIF Stachytarpeta jamaicensis(L.) Vahl - Solikin Solikin (Universitas Sebelas Maret, 2013)
Stachytarpeta jamaicensis belongs to family Verbenaceae believed to cure malaria, scabies, headaches,stimulant, tonic, expectorant and fever. The research aims to determine vegetative and generative growth of Stachytarpeta jamaicensis was conducted in Purwodadi Botanic Garden in October 2012 - June 2013 by observing 9 plants grouped in 3 replications. Seedlings with 6-12 leaves were planted in polybags with diameter 13 cm, height 16 cm filled with soil media ‘katel’ (soil stream sediment). The plants placed outside the glass house with light penetration about 20%. Growth observations conducted every week to high, leaf number, shoot/branch number, spike number, spike length, early flowering and fruit maturity of the plants. The results showed that the plant height, the leaf number, the shoot and branch and the spik s number of the plants was increasing linearly up to the age of 90 days after planting (DAP). Early and late flowering varied each 20-40 DAP and 69-83 DAP. The length of spikes growth following the sigmoid curve and the fruits mature at the age of 38 days after fertilization. Keywords: Growth, Stachytarpeta Jamaicensis, Vegetative, Generative